2006
DOI: 10.1016/j.joca.2006.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between specific tissue lesions and pain severity in persons with knee osteoarthritis

Abstract: In persons with knee OA, knee pain severity was associated with subarticular bone attrition, bone marrow lesions, synovitis/effusion, and meniscal tears. The contribution of bone marrow lesions to pain severity appeared to require the presence of bone attrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
265
10
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(293 citation statements)
references
References 25 publications
12
265
10
6
Order By: Relevance
“…Direct X-ray radiography is a suboptimal technique for demonstrating pathologies like synovitis or bone marrow edema, which underlie the joint pain. Torres et al (33) demonstrated that pain intensity correlated with erosion in subchondral bone, bone marrow lesions, synovitis, effusion, and meniscal tear, which are not demonstrable with direct X-ray imaging. Further, radiological grading of the disease could differ on the basis of individual assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Direct X-ray radiography is a suboptimal technique for demonstrating pathologies like synovitis or bone marrow edema, which underlie the joint pain. Torres et al (33) demonstrated that pain intensity correlated with erosion in subchondral bone, bone marrow lesions, synovitis, effusion, and meniscal tear, which are not demonstrable with direct X-ray imaging. Further, radiological grading of the disease could differ on the basis of individual assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This process results in increased stiffness of subchondral bone, flattening of the articular surface, and bone edema (4,6,23). In a cross-sectional study involving 143 patients, Torres et al (24) found that the severity of knee pain was correlated with flattening, BM edema, meniscal tears, and effusions. Hernandez et al (3) noted a significant correlation between the presence of knee pain and flattening (OR, 3.3; 95% CI, 2.5-4.5) in a recent study involving a Framingham OA cohort of 1627 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapists teach you ways to perform regular, daily activities, such as housework, with less pain. 15,16 The aim of this systemic review was to identify, evaluate and summarize the effectiveness of Rhus tox in management of pain in cases of OA.…”
Section: Physical and Occupational Therapymentioning
confidence: 99%